rev2025 – 2nd Resource Efficient Vehicles Conference (Graz University Library Publishing, 2026)
The 2nd Resource Efficient Vehicles Conference (rev2025), held from September 23–25, 2025, in Graz, Austria, brought together experts from academia, industry, and public agencies. It served as a platform for discussing innovative research centered on the conference theme Enabling Circular and Decarbonized Vehicle and Transport Solutions. The conference was structured around five key topics, ranging from sustainable design in the early stages of vehicle development, transforming the transportation system, and digitalization for sustainable transport solutions, to the role of societal perspectives in sustainable transport systems. The electronic proceedings of rev2025 serve as a repository of the presented contributions. The structure of the proceedings is based on the conference program.